2014
DOI: 10.1186/bcr3603
|View full text |Cite
|
Sign up to set email alerts
|

Inducible and coupled expression of the polyomavirus middle T antigen and Cre recombinase in transgenic mice: an in vivo model for synthetic viability in mammary tumour progression

Abstract: IntroductionEffective in vivo models of breast cancer are crucial for studying the development and progression of the disease in humans. We sought to engineer a novel mouse model of polyomavirus middle T antigen (PyV mT)-mediated mammary tumourigenesis in which inducible expression of this well-characterized viral oncoprotein is coupled to Cre recombinase (TetO-PyV mT-IRES-Cre recombinase or MIC).MethodsMIC mice were crossed to the mouse mammary tumour virus (MMTV)-reverse tetracycline transactivator (rtTA) st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 18 publications
1
36
0
Order By: Relevance
“…Previous studies have demonstrated that all of them are validated for use (Aguilera et al, 2011;Averous et al, 2012;Della Pietra et al, 2015;Dixon et al, 2011;Gong et al, 2015;Kim et al, 2011;Li et al, 2012;Murphy et al, 2011;Nissar et al, 2012;Rao et al, 2014;Sarkar and Zohn, 2012;Takeda et al, 2014;Tan et al, 2011;Taniguchi et al, 2011;Wu et al, 2010;Zhang et al, 2011).…”
Section: Antibodiesmentioning
confidence: 99%
“…Previous studies have demonstrated that all of them are validated for use (Aguilera et al, 2011;Averous et al, 2012;Della Pietra et al, 2015;Dixon et al, 2011;Gong et al, 2015;Kim et al, 2011;Li et al, 2012;Murphy et al, 2011;Nissar et al, 2012;Rao et al, 2014;Sarkar and Zohn, 2012;Takeda et al, 2014;Tan et al, 2011;Taniguchi et al, 2011;Wu et al, 2010;Zhang et al, 2011).…”
Section: Antibodiesmentioning
confidence: 99%
“…To further understand the spatiotemporal events leading to loss of apical-basal polarity, we examined tumors from mice expressing the polyoma virus middle-T antigen (PyMT) under the mouse mammary tumor virus (MMTV) promoter/enhancer (Lin et al 2003) or as a doxycycline-inducible system with a cross of two mouse strains: the PyMT-IRES-CRE (MIC) and the MMTV-reverse tetracycline transactivator (rtTA) (MTB) (Rao et al 2014). These mice form multifocal HR + luminal-type tumors with high penetrance (>75%) that progress through stages, including hyperplasia, mammary intraductal neoplasia (MIN), and adenocarcinoma, that are morphologically similar to human preinvasive breast lesions (Guy et al 1992;Lin et al 2003;Herschkowitz et al 2007;Rao et al 2014).…”
Section: Polarity Is Progressively Lost In a Mouse Model Of Breast Camentioning
confidence: 99%
“…These mice form multifocal HR + luminal-type tumors with high penetrance (>75%) that progress through stages, including hyperplasia, mammary intraductal neoplasia (MIN), and adenocarcinoma, that are morphologically similar to human preinvasive breast lesions (Guy et al 1992;Lin et al 2003;Herschkowitz et al 2007;Rao et al 2014). To determine whether this model resembles human cancer in regard to progressive loss of apical-basal polarity and tissue organization, we immunostained tissue sections from different stages with a panel of apical-basal polarity markers, including ZO1, Par6, aPKC, Ezrin, Ecadherin, and Dlg1 ( In hyperplasia, we observed an increase in the number and size of ducts, suggesting that branching morphogenesis is increased at the earliest steps.…”
Section: Polarity Is Progressively Lost In a Mouse Model Of Breast Camentioning
confidence: 99%
See 2 more Smart Citations